Функціонал нефінітних речень у сучасній англійській мові - Лопатюк, Наталія (Видавництво Рута, 2025)
Today's man is not only a consumer but also a producer of both material and non-material products, the latter including knowledge and information in general. The pace of modern life is reflected in everything, including the speed of receiving and providing information. Therefore, the study of ergonomic language tools is highly relevant. This article examines the functions of non-finite sentences, which serve as an extremely economical and expressive means of verbalizing thought in modern English. We assume that this characteristic explains the relatively high frequency of non-finite sentences in newspaper publications. The study is based on a corpus of 780 non-finite sentences, selected with the help of the consecutive selection method. The English online newspapers The Evening Standard and The Guardian were used as sources. The novelty of this research lies in its attempt to describe non-finite sentences containing a non-finite verb form that is not part of a predicative construction. The study's findings indicate that infinitive clauses, -ing clauses with participles and gerunds, and -ed clauses can function as subjects, extraposed subjects, direct objects, subject predicatives, adverbial modifiers, and various types of complements, depending on the elements they modify. Additionally, they can serve as postmodifiers and supplementary clauses. We assume that the predominance of active infinitive and -ing clauses suggests a preference for an active stance by the authors in conveying their messages to the reader. This, in turn, reflects the mentality of native English speakers, which places an emphasis on personal responsibility.
Keywords: function; non-finite verb forms; non-finite clauses; infinitive clauses; -ing clauses; -ed clauses